Evaluation of sodium lignin sulfonate as draw solute in forward osmosis for desert restoration - Duan, Jintang; Litwiller, Eric; Choi, Seung-Hak; Pinnau, Ingo (Journal of membrane science, 2014)
Sodium lignin sulfonate (NaLS), an abundant waste product of paper manufacturing, can be used in desert restoration. Combined with water and applied on arid land, NaLS has been shown to stabilize sand and provide a medium for plant growth. Here, we demonstrate that NaLS is an efficient draw solute in forward osmosis (FO) to extract water from impaired sources. The osmotic pressure of a 600gNaLS/kg water solution is 78bar (7.8 MPa) as measured by freezing point depression. The FO performance using NaLS draw solute was evaluated with commercial FO membranes under various test conditions. The effects of draw solute concentration, feed salinity and membrane orientation were systematically investigated. Potential ways to optimize the process, e.g. combining fertilizer draw solutes and NaLS, are proposed. [Display omitted] •A novel forward osmosis draw solute, sodium lignin sulfonate (NaLS), is proposed.•NaLS can generate high osmotic pressure.•Commercial FO membranes yield reasonable performance with NaLS in FO tests.